2019
DOI: 10.1038/s41598-019-48346-3
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Label-Free Enrichment of Rare Trophoblast Cells from Cervical Samples

Abstract: Extravillous trophoblasts (EVTs) have the potential to provide the entire fetal genome for prenatal testing. Previous studies have demonstrated the presence of EVTs in the cervical canal and the ability to retrieve a small quantity of these cells by cervical sampling. However, these small quantities of trophoblasts are far outnumbered by the population of cervical cells in the sample, making isolation of the trophoblasts challenging. We have developed a method to enrich trophoblast cells from a cervical sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Patients with a positive or suspicious result underwent cytological screening. Exfoliated cells were rinsed with 20 mL of ThinPrep PreserveCyt (Hologic, Marlborough, MA, USA) fixing solution immediately after removal of the brush from the cervix and the samples were stored at 4°C ( 51 ). These patients underwent colposcopy examination and two biopsy specimens were collected from adjacent sites in each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a positive or suspicious result underwent cytological screening. Exfoliated cells were rinsed with 20 mL of ThinPrep PreserveCyt (Hologic, Marlborough, MA, USA) fixing solution immediately after removal of the brush from the cervix and the samples were stored at 4°C ( 51 ). These patients underwent colposcopy examination and two biopsy specimens were collected from adjacent sites in each patient.…”
Section: Methodsmentioning
confidence: 99%
“…[457] Similar principles have also been applied to the sorting and analysis of rare bacterial cells within blood and urine, as well as fetal cells in prenatal diagnostics. [387,388,414,458,459] Rare cell biosensors illustrate some of the more creative nanotechnology approaches that can overcome limitations of many traditional instruments and diagnostic techniques.…”
Section: Clinical Applications Of Nanomaterials In Diagnosticsmentioning
confidence: 99%
“…Different cell types settle and adhere differently in in vitro environments, due to a combination of material interaction and mechanical properties. Bailey-Hytholt et al recently demonstrated effective rare cell selection via different settling behavior of cells in polystyrene wells [63]. This approach was used in a prenatal testing workflow for the purpose of separating rare extravillous trophoblasts from infants in utero from maternal cervical cells in cervical swabs.…”
Section: Settling and Adhesionmentioning
confidence: 99%